Motivation and impostor syndrome as factors of professional burnout - ЯБЛОНСЬКА, Тетяна; ШЕВЧУК, Анастасія (Київський національний університет імені Тараса Шевченка, 2025)
Background. The problem of professional burnout in the modern world is becoming increasingly relevant due to the growing intensity of work and high demands on specialists. Among the factors of burnout, a special place is occupied by motivational aspects and internal psychological barriers, such as imposter syndrome. The desire for professional growth is a natural driving force, but in combination with doubts in one`s own abilities, it can lead to emotional and physical exhaustion. The aim of this article is to clarify the features of motivation and the impostor syndrome as factors contributing to professional burnout among specialists. Methods. The empirical study used: “Spilberger-Khanin Anxiety Questionnaire” (Khanina Yu. L.), P. Klans Impostor Phenomenon Scale (adapted by Shevchuk A., Yablonska T.), V. Schaufeli “Vitality Check” Questionnaire (adapted by Karamushki L.), Connor-Davidson-10 Resilience Scale (adapted by Kireeva Z., Odnostalko O., Biron B.), Professional Vitality Questionnaire (Kokun, 2021-b), Mental Health Stability – Short Form (adapted by Nosenko E., Chetvertyk-Burchak A.), Professional Burnout Diagnostics (MBI-HSS, UIKPT). The Jamovi 2.3.28 statistical package was used to analyze the data. The descriptive statistics method, Kolmogorov–Smirnov criteria, Mann–Whitney and Kruskal–Wallis U-criterion, Spearman correlation coefficient were used. The sample consisted of 274 individuals over 18 years of age, of whom 82.8% were women and 17.2% were men. Results. Moderate levels of professional burnout, anxiety, impostor syndrome, professional resilience, and mental health stability were revealed, as well as an above-average level of resilience. Direct relationships between personal anxiety, perfectionism, resilience, and impostor syndrome were statistically confirmed. Based on regression analysis, a statistically significant model was obtained that explains 33.6% of the variance in data on professional burnout. According to the model, the predictors of professional burnout are perfectionism, anxiety, the motivational component of professional resilience, and imposter syndrome. In contrast, perfectionism has the strongest direct positive effect on the level of burnout. Conclusions. It was found that personal anxiety, perfectionism, resilience, and imposter syndrome are factors of professional burnout. The hypothesis that professional burnout is more severe in adolescence, which is associated with difficulties in professional formation, unstable motivation, and manifestations of imposter syndrome in young specialists, is confirmed.

Вступ. Проблема професійного вигорання в сучасному світі набуває все більшої актуальності через зростаючу інтенсивність праці та високі вимоги до фахівців. Серед чинників вигорання особливе місце посідають мотиваційні аспекти та внутрішні психологічні бар'єри, такі як синдром самозванця. Прагнення до професійного зростання є природною рушійною силою, але у поєднанні з сумнівами у власних силах може призвести до емоційного та фізичного виснаження.Метою статті є з'ясування особливостей мотивації та синдрому самозванця як чинників професійного вигорання фахівців.Методи . В ході емпіричного дослідження використано: "Опитувальник тривожності Спілбергера-Ханіна" (Ханіна Ю. Л.), Шкалу феномена самозванця П. Кланс (адап.Шевчук А., Яблонська Т.), Опитувальник "Перевірка на життєздатність" В. Шауфелі (адап. Карамушки Л.), Шкалу резильєнтності Коннора-Девідсона-10 (адап. Кірєєвої З., Односталко О., Бірон Б.), Опитувальник професійної життєстійкості (Кокун, 2021-б), Стабільність психічного здоров'я – коротка форма (адап. Носенко Е., Четвертик-Бурчак А.), Діагностику професійного вигорання (MBI-HSS, УІКПТ). Для аналізу даних використано статистичний пакет Jamovi statistical package 2.3.28. Застосовувалися метод описової статистики, критерій Колмогорова–Смірнова, U-критерій Манна-Уітні для порівняння незалежних груп, критерій Краскала–Уолліса для незалежних вибірок, коефіцієнт кореляції Спірмена. Вибірка склала 274 осіб старше 18 років, з них жінок 82,8%, чоловіків 17,2%.Резул ьтати. Виявлено помірні рівні професійного вигорання, тривожності, синдрому самозванця, професійної життєстійкості і стабільності психічного здоров'я, а також рівень резильєнтності вище середнього. Статистично підтверджено прямі зв'язки особистісної тривожності, перфекціонізму, резильєнтності й синдрому самозванця. На основі регресійного аналізу отримано статистично значущу модель, що пояснює 33.6% дисперсії даних щодо професійного вигорання. Відповідно до моделі, предикторами професійного вигорання є перфекціонізм, тривожність, мотиваційний компонент професійної життєстійкості та синдром самозванця, при цьому найсильніший прямий позитивний вплив на рівень вигорання має перфекціонізм.Висновки. Виявлено, що особистісна тривожність, перфекціонізм, резильєнтність і синдром самозванця виступають чинниками професійного вигорання. Підтверджено гіпотезу про більшу вираженість професійного вигорання в юнацькому віці, що пов'язано зі складнощами професійного становлення, нестійкою мотивацією та проявами синдрому самозванця в молодих спеціалістів.
Мотивація та синдром самозванця як чинники професійного вигорання
Keywords: professional burnout; imposter syndrome; personality motivation; perfectionism; anxiety; resilience; youthful age; професійне вигорання; синдром самозванця; мотивація; перфекціонізм; тривожність; резильєнтність; юнацький вік